2015
DOI: 10.3109/21678421.2015.1051987
|View full text |Cite
|
Sign up to set email alerts
|

Regionality of disease progression predicts prognosis in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating neurological syndrome in which motor neurons degenerate relentlessly. Although the site of onset and the rate of spread have been studied extensively, little is known about whether focal as opposed to diffuse disease affects prognosis. We therefore tested the hypothesis that regionality of disease burden is a prognostic factor in ALS. We analysed clinical data from two large multicentre, longitudinal trials. Regionality was defined as the difference in progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Taken together, these results indicate that ALSFRS-R_bulb and ALSFRS-R_motor capture the divergent clinical and prognostic characteristics of patients with spinal and bulbar onset. The observed longitudinal trend in subscores may also explain observations that increased regionality (estimated from ALSFRS-R subscores) of disease was prognostic,22 since typically the bulbar score in patients with bulbar declines very rapidly (figure 2). …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Taken together, these results indicate that ALSFRS-R_bulb and ALSFRS-R_motor capture the divergent clinical and prognostic characteristics of patients with spinal and bulbar onset. The observed longitudinal trend in subscores may also explain observations that increased regionality (estimated from ALSFRS-R subscores) of disease was prognostic,22 since typically the bulbar score in patients with bulbar declines very rapidly (figure 2). …”
Section: Discussionmentioning
confidence: 85%
“…However, by compressing multidimensional domains into one combined score, information may be lost. ALSFRS-R subscores have previously been used to quantify regionality of disease, which was seen to be a prognostic factor 22. Furthermore, it has been suggested that cognitive impairment, particularly executive dysfunction at onset, predicts a bulbar subscore decline 23.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread interest in disease prediction modeling, the current literature about the progression rates in different body regions and the reaching of clinical milestones is still relatively sparse. One of the first attempts to distinguish between overall and regional progression was a study by van der Kleij et al [18]. Using the ALSFRS-r score, they produced a model to measure the regional burden of the disease and thus predict overall survival.…”
Section: Discussionmentioning
confidence: 99%